Survival Analysis: The Impact of Key Factors on Financial Distress and Longevity of Real Estate Firms Listed on the Indonesia Stock Exchange - Sri Dwi Ari Ambarwati; Slamet Trisno Haryono; Ida Ayu Fatmayuni; Gunawan Nusanto; Agus Sukarno (The Indonesian Accounting Review, 2025)
This study uses a quantitative approach to examine the factors influencing financial distress among companies in the Property Sector listed on the Indonesia Stock Exchange (IDX) from 2014 to 2023. The research focuses on four key financial ratios: Return on Equity (ROE), Current Ratio (CR), Debt to Assets Ratio (DTA), and Total Assets Turnover (TATO), with inflation included as a moderating variable. A purposive sampling method was used to select 36 companies for the study. Survival analysis was conducted using STATA software to analyzed the data. The results reveal that ROE has a significant negative effect on financial distress, indicating that higher ROE reduces the likelihood of financial distress. In contrast, CR has a significant positive effect, suggesting that a higher current ratio is associated with increased financial distress. DTA and TATO were found to have no significant impact on financial distress. Additionally, inflation was found to moderate the relationship between ROE and financial distress, worsening financial distress when ROE is poorly managed. However, inflation does not significantly affect CR, DTA, or TATO. These findings emphasize the importance of efficient financial management, particularly concerning ROE, and the role of inflation in influencing financial distress.